CLINICAL COURSE OF THYROIDITIS AND MODERN TREATMENT METHODS (International Conference on Medical Science, Medicine and Public Health, 2025)
This thesis explores the clinical features, diagnosis, and modern treatment of thyroiditis, an inflammatory disorder of the thyroid gland. It analyzes the diverse presentations of autoimmune, infectious, and drug-induced thyroiditis, highlighting their distinct mechanisms and clinical courses. The study shows that early recognition, supported by laboratory and imaging tests, allows for targeted therapies that improve outcomes. Current treatments include immunosuppressive drugs, hormone replacement, and biologics targeting specific inflammatory pathways. The research emphasizes standardized diagnostic and therapeutic protocols to preserve thyroid function and guide clinical decisions.